Reflections on Social Responsibility in the Peruvian Company - Puell Palacios, Juan (2019)
The conceptualization of Corporate Social Responsibility (CSR) or corporate social responsibility (CSR) refers to socially responsible companies. The Green Book (2001) of the European Union (EU), defines corporate responsibility as “the voluntary integration by companies, social and environmental concerns in their business operations and their relationships with their interlocutors”. As Puterman (2011) points out, the benefits of CSR corporate image and business reputation, reducing operating costs, strengthening the capacity of organizations to recruit and retain top employees, strengthening the relationship is the community, and its environment, the strengthening of consumer loyalty, the improvement of quality and productivity, and the increase in profitability, among many others.